Vitex agnus-castus L. د ا رسة الفعالية البايولوجية لبعض مستخلصات أو ا رق نبات كف مريم - عبود شريف, علي; عبد الله الموسوي, عبدالامير; حسين علي, لؤي (University of Thi-Qar Journal of Science, 2011)
In this study, the antibacterial activity of some Leaves Extracts of (Vitex agnus-castusL.)were determinated against two species of bacteria Escherichia coli and Staphylococcusaurous, These extracts including hot ethanolic 70% extract , hot methanolic 70% extractflavonoid extract , oil extract and essential oils extracts , and the anticancer activity of flavonoidextract was evaluated against two cancer cell lines (HEP-2, AMN3 ).The results showed that flavonoid extract exhibited best antibacterial activity followed byhot ethanolic 70% extract and hot methanolic 70% extract , while oil extract and essential oilsextracts showed no antibacterial activity .Anti cancer activity of flavonoid extract showed no anticancer activity against Hep-2andAMN3 cell lines for three concentrations (3.125,6.25,12,5,25 mg/l) in comparison with negativecontrol. Moreover, a photochemical screening of the methanolic extract was revealed thatpresence of flavonoids,tannins,saponins,phenols,and carbohydrates and absence of proteins andalkaloids